THE DEVELOPMENT OF SUROBOYOAN BATIK BATIK LEARNING MEDIA BASED ON ANDROID APPLICATION AS A STRATEGY FOR STRENGTHENING LOCAL CULTURE OF THE 21st CENTURY: PENGEMBANGAN MEDIA PEMBELAJARAN IPS BATIK SUROBOYOAN BERBASIS APLIKASI ANDROID SEBAGAI STRATEGI PENGUATAN BUDAYA LOKAL ABAD KE-21 - Ilmi, Aas Nafilah (Program Studi S1 Pendidikan IPS, Universitas Negeri Surabaya, 2022)
Social Sciences becomes a benchmark for learning in general, studying a social probematics that requires the encouragement of learning media in order to reveal all aspects that occur in the surrounding environment. Under the current of globalization, humans are given more than one very difficult choice, including associating with the life of the foreign world, what would happen if every human being could only be closed to the influence of the outside world. However, a problem in international relations can make local cultural values that exist in the country become extinct so that there will be no authenticity in their cultural values. This research is a research that is under development or referred to as the R&D (research and development) method. The researcher uses a development with the ADDIE model. Because the development of this model is in line with the direction of research, which can print products in the form of learning media for Android Applications that are declared feasible based on the results of media validation analysis. The results of the research that has been carried out by researchers include an analysis of the stages, namely related to the applicable curriculum in order to obtain a core competency and basic social science competence in the material of Social and Cultural Change. Product testing was carried out to evaluate the media based on the responses given by the research subjects to the application of learning media Android applications based on Suroboyoan batik in social studies learning activities. Where the evaluation results as input to improve the quality of the media. So that the resulting product is able to change or improve student learning outcomes.